A neural circuit for sex-dependent conditioned pain hypersensitivity in mice - Mingjun Zhang; Ziyun Ni; Jun Ma; An Liu; Ying Liu; Qianqian Lou; Wan-Ying Dong; Zhi Zhang; Juan Li; Peng Cao (Nature Communications)
Abstract The neural mechanisms underlying sex-specific pain, in which males and females exhibit distinct responses to pain, remain poorly understood. Here we show that in a mouse model of male-specific pain hypersensitivity response to pain conditioning environments (contextual pain hypersensitivity model), elevated free-testosterone leads to hyperactivity of glutamatergic neurons in the medial preoptic area (GlumPOA) through activation of androgen receptor signaling, which in turn induces contextual pain hypersensitivity in male mice. Although not observed in naïve female mice, this pain phenotype could be induced in females via chronic administration of testosterone propionate. In addition, GlumPOA neurons send excitatory inputs to GABAergic neurons in the ventrolateral periaqueductal gray (GABAvlPAG) that are required for contextual pain hypersensitivity. Our study thus demonstrates that testosterone/androgen receptor signaling enhances GlumPOA → GABAvlPAG pathway activity, which drives a male-specific contextual pain hypersensitivity, providing insight into the basis of sexually dimorphic pain response.